Updated information on qualitative leaf anatomical characters of Eusideroxylon zwageri from East Kalimantan, Indonesia - ASIH PERWITA DEWI; TRI Y. I. WULANSARI; SENI K. SENJAYA; DEBY ARIFIANI; IRVAN F. WANDA; YUNITA LISNAWATI; SUNARDI SUNARDI; APRILIANA D. PRAWESTRI; IRFAN MARTIANSYAH; EVANA EVANA; RIZKY D. SATRIO; ANJALI M. N. K. HARTONO; SUYOKO SUYOKO; ADE Y. YUSWANDI; MUHAMMAD SYUKUR; DEA K. SARI; CHIKA A. RASYL (Smujo International, 2025)
Abstract. Dewi AP, Wulansari TYI, Senjaya SK, Arifiani D, Wanda IF, Lisnawati Y, Sunardi, Prawestri AD, Martiansyah I, Evana, Satrio RD, Hartono AMNK, Suyoko, Yuswandi AY, Syukur M, Sari DK, Rasyl CA. 2025. Updated information on qualitative leaf anatomical characters of Eusideroxylon zwageri from East Kalimantan, Indonesia. Nusantara Bioscience 17: 322-336. Eusideroxylon zwageri, the sole species of its genus (Eusideroxylon) and one of the most economically and culturally significant timbers of Borneo known as Bornean ironwood or “kayu ulin”, has been extensively studied for its ecology, genetics, and conservation, yet its foliar anatomy remains poorly documented. This study provides an updated qualitative assessment of leaf anatomical characters of E. zwageri based on 66 accessions representing five subpopulations in East Kalimantan, Indonesia. Transverse and paradermal sections of the lamina, midrib, and petiole were prepared following standard microtechnique procedures, and 37 anatomical traits were recorded. The results showed that most foliar anatomical features of E. zwageri are consistent with the Lauraceae family. A single character appears diagnostic for E. zwageri—osteosclereids present in the mesophyll of the lamina. Several anatomical features of E. zwageri indicate functional adaptation, including superficial stomata (related to efficient CO2 intake), sclereids (contributing to the hardness and durability of the wood), oil cell distribution (which helps prevent pest attacks), suggesting functional adaptations related to gas exchange efficiency, mechanical reinforcement, and defense against herbivory. Nevertheless, understanding pronounced lignification of sclerenchyma and sclereids may constrain regeneration, posing challenges for conservation. These updated anatomical data provide a foundation for future taxonomic, ecological, and conservation research, particularly in developing propagation strategies to support large-scale restoration of this Vulnerable species.